The Development of Mathematics e-Module to Facilitate Numeracy and Digital Literacy Skills - Hamzah Upu; Rahmat Syam; Nurhiqmah Takbir; Agusalim Juhari; Muhammad Yusran Basri (Universitas Negeri Makassar, 2024)
This type of research was Research and Development (R & D) aimed to produce teaching modules referring to the ADDIE model development process (analysis, design, development, implement, and evaluate). The test subjects was selected by purposive sampling technique from students of class 7th SMP Negeri 1 Pallangga, Gowa. The results of the assessment by the two validators is 4.5 of from the ideal score 5.0 with valid criteria. Analysis of teacher response questionnaire data on the teaching module obtained a score of 91% in the first trial and 93.8% in the second trial with the respective criteria being very practical and the teaching module implementation observation sheet showed an average score for the first trial of 1.8 and 1.9 on the second trial with the respective criteria being fully implemented so that the teaching module was declared practical. The level of effectiveness assessed from the results of learning achievement showed that 100% of students in each trial successfully exceeded the Learning Objective Completeness Criteria, the results of positive student responses above an average of 3.5 and the results of observations of student activity obtained 91.9% very active criteria in the first trial and 92.6% very active criteria in the second trial fulfilled the effectiveness criteria so that the teaching module of data and diagram material was declared effective. So it can be concluded that the teaching module of data and diagram material is valid, practical and affective to be used in learning activities.